2018
DOI: 10.1039/c8fo00018b
|View full text |Cite
|
Sign up to set email alerts
|

New highlights on the health-improving effects of sulforaphane

Abstract: In this paper, we review recent evidence about the beneficial effects of sulforaphane (SFN), which is the most studied member of isothiocyanates, on both in vivo and in vitro models of different diseases, mainly diabetes and cancer. The role of SFN on oxidative stress, inflammation, and metabolism is discussed, with emphasis on those nuclear factor E2-related factor 2 (Nrf2) pathway-mediated mechanisms. In the case of the anti-inflammatory effects of SFN, the point of convergence seems to be the downregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 150 publications
0
41
0
Order By: Relevance
“…SFN is an isothiocyanic acid mainly presenting in broccoli and other cruciferous vegetables. It has anti-tumor, anti-apoptotic, anti-oxidative, anti-inflammatory, and anti-bacterial effects [17,30,31,32]. In this study, TM3 cells were used to analyze the effect and mechanism of action of SFN in antagonizing Cd-induced cytotoxicity via its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…SFN is an isothiocyanic acid mainly presenting in broccoli and other cruciferous vegetables. It has anti-tumor, anti-apoptotic, anti-oxidative, anti-inflammatory, and anti-bacterial effects [17,30,31,32]. In this study, TM3 cells were used to analyze the effect and mechanism of action of SFN in antagonizing Cd-induced cytotoxicity via its antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%
“…On these premises, we investigated the potential effect of the isothiocyanate SFN on the modulation of AQP8 and Nox expression in the leukemic B1647 cell line. As a result of many in vivo and in vitro studies, it was stated that SFN is able to selectively exert cytotoxic effects in various human cancer cells, while having no cytotoxic effects, or being even cytoprotective in normal cells [5, 8]. The treatment of HL-60 cells with increasing concentrations of SFN (0–100 μ M) was reported to induce a dose-dependent decrease in cell viability, with a IC 50 value determined as 49.5 μ M [36]; in pre-B ALL (acute lymphoblastic leukemia) and T-ALL cell lines, it was observed that SFN induce cytotoxicity at concentration ranging from 4 to 10 μ M in contrast to 90 μ M for nonleukemic controls [37].…”
Section: Discussionmentioning
confidence: 99%
“…Among cruciferous vegetables, broccoli contains the highest concentration of the glucosinolate glucoraphanin, which is hydrolysed by myrosinase and gut microbiota, releasing sulforaphane, SFN (4-methylsulfinylbutyl isothiocyanate). In addition to its well-known anticancer activity [2], SFN has been demonstrated to possess cardioprotective [3], neuroprotective [4], and anti-inflammatory activities [5], suggesting a pleiotropic protective role for this nutraceutical compound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphoglucomutase 3 (PGM3) belongs to the hexose-phosphate mutase family, and it mediates the conversion of glucose-1-phosphate to glucose-6-phosphate, thus regulating glycolysis and pentose phosphate shunt [194]. Recently, it has been demonstrated to be a specific target for the anti-PCa activity of sulforaphane [195], an organic isothiocyanate derived from broccoli and other cruciferous plants [196,197].…”
Section: Natural Compounds Impairing Metabolismmentioning
confidence: 99%